KINERJA PETUGAS RUMAH SAKIT UMUM DAERAH DOKTER SUDARSO PONTIANAK DALAM MEMBERIKAN PELAYANAN JAMKESMAS - Nilna Siti Mislaini E.21108056 (FISIP Universitas Tanjungpura, 2013)
The quality of hospital staff in providing services to the community is one of the factors that affect the quality of the hospital itself. One form of the services provided by the hospital care is medical treatment. This study focused on employee punctuality, quality of work, time spent in providing services Jamkesmas employees, the natural ability to work, and work processes. Foci are discussed with qualitative methods and case studies in hospitals Dr. Soedarso Pontianak. From the results of the study found that the quality of the quality of work, time spent, as well as the work done in providing service officer Jamkesmas pretty good. As for the aspect of timeliness and level of employees in providing services is still less than optimal. Therefore, from a focus on time researchers suggested that disciplinary officer Jamkesmas services be improved to provide optimum services to participants Jamkesmas. As for the suggestion to focus on employee skill levels is the division of labor should be adjusted to the expertise of each officer. Key word: Performance Measurement Officer, Hospital, Care Jamkesmas